A Solvothermal Route Decorated on Different Substrates: Controllable Separation of an Oil/Water Mixture to a Stabilized Nanoscale Emulsion. (21st October 2015) - Zhang, Weifeng; Liu, Na; Cao, Yingze; Chen, Yuning; Xu, Liangxin; Lin, Xin; Feng, Lin
Abstract : A facile solvothermal route is developed to fabricate polydivinylbenzene (PDVB) and decorate the polymer onto porous substrates. "Controllable" separation can be realized by selecting substrates with different pore sizes. The PDVB‐modified mesh shows superhydrophobicity/superoleophilicity, and can be used for oil/seawater mixture separation, while the PDVB‐modified membrane exhibits high hydrophobicity/superoleophilicity, and is able to separate surfactant stabilized nanoscale water‐in‐oil emulsions.